1981
DOI: 10.1136/sti.57.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydial infection in homosexual men. Frequency of isolation of Chlamydia trachomatis from the urethra, ano-rectum, and pharynx.

Abstract: SUMMARY Urethral, rectal, and pharyngeal material from 150 men who had had exclusively homosexual contact and who consecutively attended a sexually transmitted diseases clinic was cultured for Chlamydia trachomatis. The organism was isolated from at least one site in 15 (10%) patients. The isolation rates from the urethra, rectum, and pharynx were 6 70o, 4%, and 1 3%/o respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 11 publications
0
16
1
Order By: Relevance
“…Several studies have shown that the chlamydial isolation rate from the urethras of homosexual men is less than that from heterosexual men,78 and that rectal infection associated with C trachomatis is less common than urethritis caused by C trachomatis. [1][2][3] McMillan et al suggested that pharyngeal and rectal mucosa are less well suited than genital sites' to colonisation by chlamydiae.' Though the numbers of isolates obtained in our study were too small for us to draw any firm conclusions, we believe that direct immunofluorescence is an acceptable alternative technique to culture and that the IDEIA test is unsuitable for non-genital sites.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the chlamydial isolation rate from the urethras of homosexual men is less than that from heterosexual men,78 and that rectal infection associated with C trachomatis is less common than urethritis caused by C trachomatis. [1][2][3] McMillan et al suggested that pharyngeal and rectal mucosa are less well suited than genital sites' to colonisation by chlamydiae.' Though the numbers of isolates obtained in our study were too small for us to draw any firm conclusions, we believe that direct immunofluorescence is an acceptable alternative technique to culture and that the IDEIA test is unsuitable for non-genital sites.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, micro-organisms known to be pathogenic or suspected of pathogenicity in the male urethra may be transmitted to the rectum and it is possible that some cause proctitis. Chlamydia trachomatis which appears to cause 50% of cases of non-gonococcal urethritis (NGU) has been isolated sporadically from the rectum (Darougar et al, 1972;Goldmeier and Darougar, 1977;McMillan, Sommerville and McKie, 1981) but its association with NGP is unknown. Ureaplasma urealyticum may cause a proportion of cases of NGU and can be isolated from the anal canal of females without difficulty (Munday, Furr and Taylor-Robinson, 1981) but there are no reports of the micro-organism having been isolated from the rectum of male homosexuals.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Quinn et al isolated chlamydiae from 14 (8%) of 171 homosexual men and described a wide range of conditions from severe ulcerative proctitis to asymptomatic infection. 2 The evidence presented suggested that severe disease was produced by lymphogranuloma venereum (LGV) serovars of C trachomatis, whereas milder disease was produced by oculogenital serovars.…”
Section: Introductionmentioning
confidence: 99%